Research statement: inference of human-computing algorithms from massive-scale educational interventions - López y Rosenfeld, Matías (2014)
The main goal of the present research statement is to develop an educational computerized framework able to detect in which tasks a child has difficulties and generate a personalized intervention based on automatic observation and evaluation of data, as part of an interdisciplinary project at the crossroads of Computer Science, Cognitive Science, Biology and Psychology. (Párrafo extraído del texto a modo de resumen)